REVITALISASI FUNGSI PARIWISATA KALI UNDA SEBAGAI UPAYA PENINGKATAN EKONOMI DESA PAKSEBALI, KECAMATAN DAWAN, KABUPATEN KLUNGKUNG - Setem, Wayan; Gulendra, I Wayan; Yudha, I Made Bendi; Kariana, I Nengah; Putra, Anak Agung Ramanda (Institut Seni Indonesia Surakarta, 2024)
Paksebali Village is one of 12 villages in Dawan District, Klungkung, Bali, which is one of the supporting villages for winning Adi Pura, which has natural resource potential in the form of the Kali Unda tourism object. The problem that occurs, the potential of human resources, namely the surrounding community, does not optimize and utilize the existing natural potential. Poor management of facilities makes this tour less attractive to visitors. The background is that the management of the Kali Unda tourist attraction has not been optimal so that it has an impact on the lack of interest of tourists to visit and this also has an impact on the absence of locally-generated revenue (PAD) from tourism activities. This community service is to revitalize the tourism function as an effort to improve the economy of Paksebali Village, Dawan District, Klungkung Regency. The ABCD (Asset Based Community Development) method used in the implementation of this community service consists of five key steps, namely discovery, dream, design, define and destiny. The aim of revitalizing the Kali Unda tourist area is an effort to organize the area to restore the vitality of the area which has declined by building reflection therapy ponds, fish nursery ponds, ornamental fish ponds, self-photo spots, goldfish statues, dragon statues, and mural art. The impact of the development and improvement of the function of facilities and infrastructure is able to influence the increase in tourist visits which also has an impact on people's welfare.